2015
DOI: 10.2147/ccid.s83248
|View full text |Cite
|
Sign up to set email alerts
|

Study of lipid profile in adult women with acne

Abstract: ObjectiveThe aim of this study was to establish the lipid profile of female patients with acne in the Acne-in-Adult-Women Ambulatory Care Clinic in order to observe the prevalence of dyslipidemia in those patients.MethodsThis is a retrospective transversal study that evaluated the medical records of 416 patients who attended at the Acne-in-Adult-Women Ambulatory Care Clinic, at the Dermatology Department, Faculdade de Medicina do ABC, Santo André, São Paulo, Brazil, in the year 2012. Relevant data included age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
3
12
1
Order By: Relevance
“…Furthermore, he said there was no significant difference between the grade of acne and patients' lipid profile, which was in agreement with our result. 23 As mentioned above, many studies have revealed lipid profile changes in acne patients, but, on the other hand, a few other studies showed similar values for lipid profile parameters in patients and controls. Ekiz et al reported that there was no relationship between acne and thyroid function, TG, TC, and LDL.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, he said there was no significant difference between the grade of acne and patients' lipid profile, which was in agreement with our result. 23 As mentioned above, many studies have revealed lipid profile changes in acne patients, but, on the other hand, a few other studies showed similar values for lipid profile parameters in patients and controls. Ekiz et al reported that there was no relationship between acne and thyroid function, TG, TC, and LDL.…”
Section: Discussionmentioning
confidence: 89%
“…We did not find any statistically significant association between acne severity and lipid profile. Romanska‐Gocka et al 29 and da Cunha et al 6 in their studies reported no association between acne severity and lipid profile. Our results were consistent with their results.…”
Section: Discussionmentioning
confidence: 87%
“…Our results were consistent with their results. However, both these studies included patients with age ≥20 years 6,29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations